Trivial knocks and treatment knock-outs – the challenges facing those treating childhood haemophilia. (24th May 2012) - Klauser, A; Oswald, R; Thomas, A
Abstract : Aims: Through this case presentation of a nine month old with severe haemophilia A, we have highlighted some the major challenges encountered in diagnosing and managing a significant head injury in a child of this age with a bleeding disorder. Methods: We reviewed the case history of a dizygotic, diamniotic twin who was identified early in the neonatal period as having severe haemophilia A. Months later he attended the A&E department having had an unwitnessed head injury. After clinical examination and discussion with the haematology consultant on call this was felt to be a trivial injury and he was discharged home with appropriate advice. Five days later he was readmitted fitting. A CT scan showed a large left temporoparietal haematoma with significant midline shift. As a known severe haemophiliac a factor VIII infusion was commenced. Factor VIII levels where well maintained at 100 percent for eleven days but peripheral intravenous access was increasingly difficult to maintain. A portacath was inserted to facilitate factor administration, but it became apparent there was an increasing factor VIII requirement to maintain adequate levels. Analysis of his blood revealed low level factor VIII inhibitors had developed. Days later he became sleepy with an increased head circumference. A MRI revealed obstructed hydrocephalus requiring urgent VP shunt insertion. Two hourly recombinant factor VII was used for haemostasis during and several days post procedure. At this point immune tolerance was commenced by administering large doses of factor VIII on a daily basis. Results: The infant is at home and well with his family. Revised head injury protocol for patients with severe haemophilia; any child with an unwitnessed head injury will now receive recombinant factor replacement. How vigilant monitoring of factor levels alerts clinicians to inhibitor development, allowing for alternative means of establishing haemostasis to be implemented in a safe and timely manner. Conclusion: This case provides a condensed overview of Haemophila A. From its diagnosis, through to managing some of the most severe complications associated with living with a severe bleeding disorder and the treatments we have available to us.